Complete chloroplast genome of Anathallis obovata (Orchidaceae: Pleurothallidinae) - Silvério Righetto Mauad, Anna Victoria; do Nascimento Vieira, Leila; Bolson, Mônica [UNESP]; de Baura, Valter Antônio; Balsanelli, Eduardo; Maltempi de Souza, Emanuel; Toscano de Brito, A. L.V.; de Camargo Smidt, Eric (Springer Nature, 2019)
Anathallis (Pleurothallidinae) is a Neotropical orchid genus with over 150 species. Although previous phylogenetic studies suggest the polyphyletism of the genus, there is little information about the group in the literature due to the lack of Anathallis-focused molecular studies and the absence of genomic research in Pleurothallidinae. Here, we sequenced and characterized the complete chloroplast genome (plastome) of Anathallis obovata (Lindl.) Pridgeon & M.W. Chase, the type species of the genus. In addition, we compared its structure and gene content with two Pleurothallidinae species: Masdevallia coccinea Linden ex Lindl. and Masdevallia picturata Rchb. f., and one Laeliinae: Cattleya coccinea Lindl. The plastome of A. obovata is 155,515 bp in length, with a typical quadripartite structure presenting the following measures: LSC with 83,694 bp, IRs with 26,949 bp each and SSC with 17,923 bp. The genes accD, ndhA, ndhB, ndhF have premature stop codons that may be related to a pseudogenization process and probably produce non-functional proteins. The whole-genome alignment of the four plastomes showed no structural variations when comparing Pleurothallidinae and Laeliinae species, but we detect deletion of the ndhF, ndhA, ndhI genes and a reduction in length of ndhH and ndhG in Cattleya crispata. In addition, we observed some differences in the IR borders: the IR/SSC boundary is just within the coding sequence of ycf1 in Pleurothallidinae, creating a short ycf1 fragment in IR, but in Cattleya crispata the SSC contains almost the whole ycf1 gene. These divergences observed between the plastomes of Pleurothallidinae and Laeliinae are possibly intrinsic to the evaluated subtribes.
Keywords: accD; Epidendroideae; NADH; NGS; ycf1